Respostas

2014-06-03T08:35:12-03:00
Racionalize o denominador das expressoes:

a)   2     b)   2   
  3+√7    √6-√2

        2
a) -----------
     3 + 
√7

      2            2(3 - √7)                 6 - 2√7                    6 - 2√7       6 -2√7      6 - 2√7
-------------- = -------------- =     ----------------------------- = -------------------= ----------- = -----------
3 + √7        (3+√7)(3-√7)     3.3 -3√7 +3√7-√7√7         9 -  √7²        9 - 7            2




6 - 2√7  : 2          
--------------- =   3 - √7
    2      : 2



b)   2   
√6-√2


    2             2(√6 + √2)                         2√6 + 2√2                    2√6 + 2√2
---------- = -------------------------  =  ----------------------------------------=  -----------------------------
√6 - √2      (√6-√2)(√6+√2)       √6√6 + √6√2 -√2√6 - √2√2    √6² + √12 -√12 -√2²


2√6 + 2√2       2√6 + 2√2        2√6 + 2√2   : 2         √6 + √2
---------------- = -----------------  =   ----------------------- =      ------------
  6 + 0 - 2             4                        4        : 2              2